Technical systems and the architecture of transnational business governance interactions. Issue 1 (18th April 2013) - Porter, Tony
Abstract This article sets out the concept of a technical system and explores its ability to explain why some transnational regulatory domains are governed by a single transnational business governance (TBG) scheme, while in others there are many such schemes. By linking the numbers of TBG schemes that govern any particular transnational regulatory domain to technical systems in this way, important insights are provided into TBG interactions. Where technical systems are present, the TBG schemes that govern them will be specialized and complementary, rather than competitive. More generally, a technical systems approach illuminates the set of extended relationships that connect TBG schemes to the industry they seek to regulate. By tracing out these relationships we can reveal indirect interactions between TBG schemes that may be mediated through firms or market infrastructures. These indirect interactions can be obscured by approaches that only focus on the direct interactions among TBG schemes. The article analyzes two cases of TBG schemes in global finance. The first, derivatives, has a single overall TBG scheme. The second case, professional financial designations, has multiple competing TBG schemes.